Robust spoken term detection using partial search and re-scoring hypothesized detections techniques - Pham, Van Tung (2019)
This research focusses on Spoken Term Detection (STD) which aims to detect a textual keyword in a speech corpus. A typical STD system relies on an Automatic Speech Recognition (ASR) system to transform the speech corpus to intermediate textual representations such as 1-best transcriptions or lattices of word and subword for indexing/retrieval. However, the imperfect modelling of ASR results in two types of error, i.e. missing and false alarm. This thesis aims to address both type of errors.